Conversores de alto ganho de tensão e estágio único aplicados à sistemas de energias renováveis com baterias - Praça, Paulo Peixoto (2011)
Taking into account the great technological development on renewable energy systems and their applications on power electronics, this work presents a new concept of converters applied to renewable systems and batteries charging with a reduced number of energy processing stages. This work approaches three different high voltage gain converters topologies with only one processing stage, and with bidirectional capability, with batteries, and with photovoltaic panels. The operation of these converters allow that the inputs (PVpanels or batteries), work independently or simultaneously, in order to compose a single DC bus. Also, proposed topologies present natural soft-switching operation. At last, the three prototypes were developed to work with a nominal power of 500W, validating the operation principle of the proposed system, featuring high efficiency, high voltage gain, and good voltage regulation on the DC bus.